Community Satisfaction with the Services of DPRD Members in Bantaeng Regency - Alamsyah Sahabuddin; Andi Agustang; Andi Muhammad Idkhan (Program Pascasarjana Universitas Negeri Makassar, 2022)
This study aims to measure public satisfaction with the services of the Bantaeng Regency DPRD based on the duties and functions, namely: the function of forming a regional regulation, the function of the budget, and the function of supervision. This study uses a quantitative method with non-probability sampling technique, the measurement with a Likert scale involves 100 respondents, namely: NGO/NGO/Youth Organization activists, lecturers, students, journalists/journalists, civil servants (PNS) and entrepreneurs. purposive sampling. The results showed that the service of the DPRD Bantaeng Regency was categorized as unfavorable at 73.84, with service quality C. DPRD Bantaeng Regency services based on the function of forming a regional regulation were categorized as poor, namely 73.74 with service quality C. DPRD Bantaeng Regency services based on the budget function were categorized as poor. good at 73.92 with service quality C. And Bantaeng Regency DPRD services based on the supervisory function are categorized as bad at 73.88 with service quality C.